Agroecology as a parameter of environmental challenges - Bessa, Marcio Moacir; Ventura, Matheus Vinicius Abadia; Oliveira, Marcia Rodrigues de; Costa, Estevam Matheus (Multitemas, 2019)
Agriculture is a complex activity, involving not only food production and technological factors, an endowment of natural resources and capital impulses, but also a series of processes associated with the effects it produces on society and ecosystems. This article presents an idea that agroecology is an environmental science, a definition of agroecosystem, an example of agroecology and discursive derivation of political and social nature that inspires this science, examining some fields of autonomous analysis and articulation with other disciplines and areas of the knowledge. Finally, interdisciplinary, agroecological and methodological school meanings are explored in ecology, culture, and environmental purposes and as an object of study of agroecology and derivation of political discourse and social health.